Danger Flash for Southwest - Bullock, Alice; O'Brian, Tony (The New Mexican, 1973)
Authentic old Indian Jewelry and prices from collectors.
2 sided/2 paged Newspaper article
Master list item #: 10
File location is in the New Mexico file Cabinet
Keywords: Indian Jewelry; Indian Art; Jewelry collectors; Jewelry pricing